Enhancement of artificial intelligence learning using Quizizz AI for SMA Negeri 3 Semarang teachers - Aisyiah Al Adawiyah; Sri Handayani; Ria Fitrasih; Novi Kurniawati; Yanuar Lutfi Rohman (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2025)
Digitising learning is a strategic approach to preparing students for the digital era, including through the use of AI. As facilitators, innovators, and mentors in the learning process, teachers at SMA Negeri 3 Semarang require digital competencies and the ability to effectively integrate technology into their teaching to make it more interactive, flexible, and tailored to students’ needs. AI learning enhancement training was provided to 25 teachers over two days, focusing on using AI in the Quizizz application to improve AI-supported learning. The activities were carried out using the following methods: (1) Socialization; (2) Training; (3) Technology implementation; (4) Mentoring and evaluation; and (5) Program sustainability. Based on the training session, teachers demonstrated a high level of engagement, with 88 percent (22 participants) completing all tasks. Teachers actively created Quizizz accounts, developed quizzes, and used Quizizz AI features. A subsequent questionnaire indicated that 18 teachers who previously lacked understanding of Quizizz AI and 15 who felt unable to create and edit questions became proficient. Thus, the training had a positive impact on enhancing teachers’ digital competencies and readiness to implement AI-based learning.